What They Don't Teach You about Artificial Intelligence at Business School: Stagnation, Oil, and War - Wim Naudé (Institute of Labor Economics (IZA), 2024)
This paper discusses four dimensions of the economics of AI that are neglected in business school and university teaching and research. First, students are not being taught that there is no 4th Industrial Revolution; on the contrary, the narrative of the inevitability and wonders of the 4IR is a vital staple of the curricula. Second, students are rarely told that we do not live in a technologically disruptive era; on the contrary, the mantra of "disrupt or else be disrupted" in a world of ceaseless innovation is drummed into students. Third, little is discussed about AI's scaling problem - it faces ecological constraints due to being an energy and water guzzler. Fourthly, business schools largely fail to create awareness that AI has essentially become a project of platform capitalism (techfeudalism) and that the last extraction zone it is being applied to is the Military Industrial Complex (MIC), in furtherance of the Permanent War Economy. Implications for AI governance and business school teaching and research are drawn from this big picture.
Keywords: P18; P17; N40; Q55; O33; 330; Artificial Intelligence; capitalism; economic growth; climate change; war